Mexico : Financial Sector Assessment Program Update; Technical Note; Organizational Arrangements for Effective Financial System Regulation, Supervision and Policymaking. (IMF Staff Country Reports; Country Report, 2007)
This paper discusses Mexico's organizational arrangements for effective financial system regulation, supervision and policymaking. Reforms implemented encompassed the legal framework, operational arrangements, and information systems, as well as transparency and information disclosure aspects. There has been a significant modernization of the regulatory framework, improvement of interagency coordination, and significant steps have been taken toward consolidated supervision. There is also the need to strengthen the Secretary of Finance and Public Credit's role in designing medium- and long-term development strategies for the financial sector attuned to evolving market realities.